Animosity Toward a Country in the Context of Destinations as Tourism Products. (September 2019) - Campo, Sara; Alvarez, Maria D.
The study aims to test a scale of consumer animosity that includes more general causes than those currently covered in the literature and examines the effects of animosity on country destination evaluations and on the intention to visit the place. The research examines the animosity construct, delving into its causes. The results confirm that consumer animosity toward a given country is a multidimensional construct formed by various causes, such as the country's perceived human rights violations and political system, its people and culture, its history and military interventions, and its economic relations with other countries. The findings also indicate that animosity influences the intention to visit the place directly and indirectly through the evaluation of the country as a tourist destination.